Dataset of the construction and characterization of stable biological nanoparticles - Gisonno, Romina Antonela (2020)
This article shows the dataset of clearance assays and the reconstitution of stable biological nano-complexes using both detergent-assisted and spontaneous solubilization of phospholipids by the recombinant purified apolipoprotein A-I (apoA-I). Protein was intra-chain crosslinked in order to introduce steric constrains. Then, native and crosslinked protein function was evaluated by a data collection of dimiristoyl phosphatidyl choline (DMPC) micellization curves. Additionally, resulting particles from spontaneous or detergent-assisted lipid solubilization were characterized by transmission electron microscopy (TEM), size exclusion chromatog-raphy (SEC), and native polyacrylamide gel electrophoresis (PAGE). Here we set up an experimental design that may help study protein structure based on its function, since interaction with biological membranes and lipids is an intrinsic activity attributed to many proteins in circulation. In addition, by t-test analysis of collected-data, we examined the formation of lipoprotein particles by native and intra-chain crosslinked proteins under different conditions like temperature and time incubation. Thus, data shown here strengthen the usefulness of an easy, rapid, accessible and inexpensive approach to test protein flexibility related to its function.